Improving E-Book Learning Experience by Learning Recommendation - Fergyanto E. Gunawan; Benfano Soewito; Sevenpri Candra (IAES Indonesia Section, 2017)
Technology Enhanced Learning is one of the most dynamic areas of inquiry in education. One form of TELs, that is on-screen learning, has become the topic of interest of many works. It is popular mainly with young people despite all ﬁndings, which undoubtedly suggest that it is detrimental to learning. The method hinders learning experience due to the reading spatial instability, difﬁculties in establishing mental map, and poor visual ergonomics. Currently, many textbooks are available in electronic form and a majority of the students in Bina Nusantara University in Indonesia, for example, consider the form to be more convenient and preferable. In the electronic form, the textbooks are much more affordable. They can be obtained easier than the printed books. This work intends to explore a method of improving the learning quality of the electronic textbooks. The improvement is expected to be achieved by enriching the electronic textbook with cues in the form of margin notes, highlights, markers, lines and arrows, and navigation tools provided by the subject matter expert. The idea is implemented on a class at the university and its effects are assessed. The participants are divided into two groups having the same distribution of the past academic performance where one group is assigned to learn using the recommendation system and the other is without the system. After the learning, their understandings are assessed systematically by qualitative and quantitative methods. The participants with the recommendation system outperform those without signiﬁcantly, which is marked by the values of the Cohen’s effect size d larger than 1.20 with the standard deviation about 0.563.